Analisis Perencanaan Pembelajaran di MAN 2 Padang - Adilah Filzhah; Nita Putri Utami (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Systematic mathematics learning planning is very important in supporting the achievement of student competencies, especially in the implementation of the Independent Curriculum. This study aims to describe the process of planning Mathematics learning at MAN 2 Padang City in the context of implementing the Independent Curriculum and the 2013 Curriculum. The method used is a qualitative approach with a descriptive design. The research instruments are in the form of interview guidelines and observation sheets. Data collection techniques are carried out through in-depth interviews with Mathematics teachers and the Deputy Head of Madrasah for Curriculum, as well as direct observation of learning planning documents and activities. The results of the study show that the planning stages start from the preparation of the Madrasah Operational Curriculum (KOM), academic calendar, details of effective weeks, Annual Program (Prota), Semester Program (Promes), analysis of CP, TP, KD, and KI, preparation of KKTP and KKM, to the development of Learning Objective Flow (ATP) and syllabus. Although planning has been carried out systematically and collaboratively, teachers still face challenges in developing contextual ATP and compiling an applicable syllabus. Thus it can be concluded that the Learning planning is very effective, namely 91.74%. Therefore, further training is needed to improve the quality of learning planning based on the Independent Curriculum.